2017
DOI: 10.1016/j.antiviral.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 suppresses the infection of porcine enteric coronaviruses and rotavirus by activating STAT3 signal pathway

Abstract: Interleukin-22 (IL-22), a member of the IL-10 superfamily, plays essential roles in fighting against mucosal microbial infection and maintaining mucosal barrier integrity within the intestine. However, little knowledge exists on the ability of porcine IL-22 (pIL-22) to fight against viral infection in the gut. In this study, we found that recombinant mature pIL-22 (mpIL-22) inhibited the infection of multiple diarrhea viruses, including alpha coronavirus, porcine epidemic diarrhea virus (PEDV), transmissible g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
2
41
1
Order By: Relevance
“…By demonstrating that IL-22 signaling is necessary and sufficient to drive epithelial claudin-2 upregulation in C. rodentium infection, these data link the previous observations and lead to the conclusion that IL-22-mediated claudin-2 expression occurs via a STAT-dependent process. Although IL-22 has not been previously recognized as a regulator of claudin-2 expression, other effects of IL-22-dependent epithelial STAT3 signaling, such as inhibition of enteric viral infection, might also reflect claudin-2 upregulation (Xue et al, 2017). Thus, claudin-2-mediated water efflux may be a widely used mechanism of innate defense.…”
Section: Discussionmentioning
confidence: 99%
“…By demonstrating that IL-22 signaling is necessary and sufficient to drive epithelial claudin-2 upregulation in C. rodentium infection, these data link the previous observations and lead to the conclusion that IL-22-mediated claudin-2 expression occurs via a STAT-dependent process. Although IL-22 has not been previously recognized as a regulator of claudin-2 expression, other effects of IL-22-dependent epithelial STAT3 signaling, such as inhibition of enteric viral infection, might also reflect claudin-2 upregulation (Xue et al, 2017). Thus, claudin-2-mediated water efflux may be a widely used mechanism of innate defense.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, shown that the expression level of IL-8 was up-regulated after PEDV infection of the host which may be beneficial for leukocyte accumulation during the inflammatory process triggered by PEDV infection. Xue et al [34] found that recombinant mature pIL-22 (mpIL-22) inhibited alpha coronavirus replication such as PEDV, transmissible gastroenteritis virus (TGEV) and porcine rotavirus (PoRV). In our study, the expression of IL-22 in porcine intestinal mucosa after PEDV infection was increased by 6.1 times compared with the mock infection.…”
Section: Discussionmentioning
confidence: 99%
“…TGEV strain H87, derived from the virulent strain H16 (GenBank accession number FJ755618), was propagated in ST cells. A TGEV stock was prepared and titrated as previously described (56). For TGEV infection, ST cells were infected with TGEV H87 at the desired MOI or mock infected with DMEM.…”
Section: Methodsmentioning
confidence: 99%